The effects of neoadjuvant chemotherapy and interval debulking surgery on body composition in patients with ovarian cancer. Issue 1 (11th November 2020) - Vitarello, John; Goncalves, Marcus D.; Zhou, Qin C.; Iasonos, Alexia; Halpenny, Darragh F.; Plodkowski, Andrew; Schwitzer, Emily; Mueller, Jennifer J.; Zivanovic, Oliver; Jones, Lee W.; Cadoo, Karen A.; Konner, Jason A.
Abstract: Background: The aim of this study was to quantify changes in body composition during ovarian cancer treatment and relate these changes to rates of complete gross resection (CGR). Methods: One hundred two patients with stage III or IV ovarian cancer who underwent neoadjuvant chemotherapy (NACT) followed by interval debulking surgery were a part of a prospectively collected database that included computed tomography scans at three time points—diagnosis, following NACT, and following debulking surgery. Skeletal muscle, visceral adipose, and subcutaneous adipose tissue volumes were obtained from a 30‐mm volumetric slab beginning at the third lumbar vertebrae. Results: Following NACT, skeletal muscle volume was significantly reduced (352.5 to 335.0 cm 3, P < 0.001), whereas adiposity was unchanged. Body mass index (BMI) and skeletal muscle volume were significantly lower in patients who achieved CGR ( P < 0.05). When these patients were stratified by BMI, the significant association of skeletal muscle to CGR was limited to patients with a BMI < 25 kg/m 2 ( P = 0.007). Conclusion: Skeletal muscle volume was significantly reduced in patients undergoing NACT for ovarian cancer. Non‐overweight patients were more likely to achieve CGR if they had lower skeletal muscle volume. Use of volumetric‐based measurement for ascertaining body composition should be explored further.